ظاهرة الهجرة غير الشرعية، ومسؤولية المجتمع الدولي في مواجهتها دراسة حالة ليبيا وتأثير الهجرة على سيادتها واستقرارها وعلاقاتها مع الدول المجاورة - أيوب، أنور المبروك حسين (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
The aim of this research is to identify the phenomenon of illegal immigration and the responsibility of the international community toward this phenomenon as well as the reasons, motives and justifications of illegal immigration and study their effects on the Libyan situation and its relationship with neighboring countries. The researcher followed the inductive method and the comparative method to extrapolate the sources related to illegal immigration. This study is based on the definition and clarification of the violation of national sovereignty in light of the growing phenomenon of illegal immigration, especially between the Libyan and Italian ports after the Libyan revolution on February 17. As well as to compare the extent to which the phenomenon of illegal migration and the violation of national sovereignty are linked. The research focused on the Libyan situation where the countries exporting the illegal immigrants to Libya considering that Libya is of the closest countries to the European ports as well as the existence of gangs smuggling people who receive the funds and facilitate the illegal access of illegal immigrants to European ports, which may affect the sovereignty of the state Libya's security stability and its obligations under international treaties and conventions. On the other hand, illegal immigration may constitute a flagrant violation of national sovereignty. The presence of human smugglers, smuggling gangs, money laundering and gangs of trafficking in human organs would cause a major disruption in international relations between Libya and its international partners. Libya is one of the countries that has signed international agreements regarding illegal immigration. The researcher reached many conclusions, including the historical development of illegal immigration and the stages of illegal immigration from its inception after the Second World War to the stage of encouraging emigration by European countries to achieve the development goals in these countries to the stage of stopping and fighting migration. It has been shown that national sovereignty can be affected as human smugglers and money-laundering perpetrators pose a significant threat by circumventing and obtaining funds directly or indirectly in exchange for facilitating illegal immigrants from reaching the European coast without right and without legal basis. Serious efforts to curb the phenomenon of illegal immigration will fail if security solutions are coupled with realistic pragmatic solutions that will support the economies of developing countries and promote a culture of human rights and individual access to all their political rights. European policies towards settling and reintegrating illegal immigrants in European societies would also solve part of the crisis of European countries in the problem of human resources shortages, but they could not limit the phenomenon of illegitimacy.